Household returns to land transfers in South Africa: A Q-squared analysis - Christine Valente (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2009)
The South African land reform programme has been widely criticised for its slow pace as well as its apparent lack of contribution to poverty reduction. However, there is little systematic evidence of the impact of land transfers on their beneficiaries due to data scarcity. This paper combines econometric evidence based on official household surveys with qualitative data collected specifically to triangulate and complement the econometric analysis. The qualitative data analysis confirms the plausibility of the econometric finding that, on average, beneficiaries do not gain from participation, and suggests that the main reason for the disappointing impact of participation is the incompatibility of consultant-led land use plans to land grantees' skills.
Keywords: 330; Land reform; South Africa; Q-squared analysis; Food insecurity; Bodenreform; Armutspolitik; Privater Haushalt; Wirkungsanalyse; Südafrika